Cheshire, Fifoot & Furmston's Law of Contract - Michael Furmston (Oxford Universitry Press, 2012)
Now in its sixth edition, The Law of Contract provides a comprehensive and authoritative treatment of all aspects of the law of contract. It differs from other texts on the topic by offering a fresh, new approach to the area. Accessible and authoritative, The Law of Contract is designed specifically to meet the needs of the modern practitioner.